Importance of environmental geotechnics - O'Kelly, Brendan; Johnston, Paul (My University, 2016)
Importance of environmental geotechnics
PUBLISHED
Keywords: environment; pollution; sustainability; Smart & Sustainable Planet; Environmental engineering